Integrated kitchen design and optimization based on the improved particle swarm intelligent algorithm. (11th March 2020) - Sun, Xin; Ji, Xiaomin
Abstract: The layout and design of the integrated kitchen can affect the efficiency of people's cooking work greatly. An excellent integrated kitchen design requires each kitchen cabinet module to meet certain constraints and reach the highest work efficiency in a certain space. In this article, we proposed an improved particle swarm intelligence algorithm (IPSO, for short) method by initializing the population chaos, dynamically improving the inertia weight and adjusting the acceleration factor, and applied in the kitchen design and optimization. This method combines the mathematical intelligent algorithm with the integrated kitchen design for the first time, and further selects the optimal design scheme from the preliminary schemes according to the fitness curve of the kitchen mathematical model, which provides the theoretical basis for the refined design of kitchen products. The method can also be used in home design, interior design, and other related areas.